Kochar's concise textbook of medicine - Kutty, Kesavan (William and Wilkins, 1998)
Medical College of Wisconsin, Milwaukee. Revised edition of: Concise Textbook of Medicine, c1990, edited by Mahendr Kochar. Text written by practicing physicians for medical students and residents. For use during and after the internal medicine clerkship. Color and halftone illustrations. Previous edition: c1989. Trim size: 10 x 7 inches. Softcover. DNLM: Internal Medicine.